Le football professionnel européen dans un système capitaliste financiarisé en crise : une approche régulationniste des facteurs de changement institutionnel - Jérémie Bastien (Revue de la Régulation)
This thesis deals with the financial crisis within European professional football. From the beginning of the 2000s, the phenomenon of ’crisis’ has been labelled by sports economists to point out the financial status of many professional football clubs that have gone worse during the years. Such phenomena raised particular interests of research about the persistency of this crisis. My main hypothesis is that European professional football is not going through a durable status of ’crisis’, but is based on an ‘unstable’ growth system. From a meso-level analysis within a regulationist framework, I end up characterising a ’financialiased’ economic system of European professional football. I claim that the instability of this system is explained by two endogenous factors – which are the ’financialisation’ of the strategies of traditional football actors and the particular status of the wage ratio – and by two exogenous factors – which are the ’instrumentalisation’ of football by ’financialised’ actors and the impact of the global crises on football.